Preparation method and application of polyesteramine quasi-solid polymer electrolyte

By in-situ thermal polymerization inside the battery, the polymer skeleton with special functional groups is used to solve the problem of poor interface contact, and the comprehensive performance of high ionic conductivity and high ion mobility is achieved.

CN119601760APending Publication Date: 2025-03-11HUBEI THREE GORGES LAB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411610126.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing quasi-solid polymer electrolytes have poor interface contact due to the preparation method and ion transport problems, making it difficult to meet the high ion conductivity, high ion mobility and good contact between electrode materials at the same time.

Method used

The quasi-solid polymeric electrolyte is prepared in situ inside the battery by thermal polymerization. By introducing a polymer skeleton containing special functional groups, the interface contactability and ion transport efficiency are improved.

Benefits of technology

A new flexible battery with good comprehensive performance has been developed in the lithium/sodium ion battery system, with a stable interface layer, a wide electrochemical window and a high ion migration number.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601760A_ABST
    Figure CN119601760A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of quasi-solid polymer electrolyte of lithium ion batteries, and particularly provides a preparation method and application of polyesteramine mixed-base polymer electrolyte. The polymer electrolyte is injected into the battery in a precursor solution manner in a similar electrolyte manner, and in-situ thermal polymerization is performed in the battery to form the quasi-solid polymer electrolyte. The precursor solution is a solution formed by uniformly mixing a polymer monomer, an electrolyte salt, a small amount of a solvent and an initiator according to a certain proportion. Wherein the monomer is one or more of phosphonate or acrylate compounds containing unsaturated bonds and amide compounds with double bonds as end groups. Functional groups are introduced into an in-situ polymerized polyester amine-based electrolyte system, a highly-crosslinked polymer structure is formed, and the method has the advantages of being simple and convenient to operate, good in safety, high in ionic conductivity, high in ionic transference number, stable in electrochemical window and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of polymer quasi-solid polymer electrolytes, and more specifically, provides a precursor solution, a preparation method of a polyesteramine quasi-solid polymer electrolyte and applications thereof. Background Art

[0002] Electrochemical energy storage has the characteristics of pollution-free operation and high charge and discharge efficiency, and has developed rapidly in recent years. Batteries, as the most representative electrochemical energy storage devices, are considered to be more suitable for large-scale energy storage and can be deployed in homes and cities far away from the power grid and in places that traditional power infrastructure cannot reach. With the development of electric vehicles and green energy, batteries with high specific energy and safety advantages have been faced with unprecedented opportunities and challenges. Currently, lithium-ion batteries using graphite anodes have almost reached the limit of specific energy. Lithium metal anodes have the characteristics of large theoretical capacity (3860 mAh g-1), small standard electrochemical potential (3.04 Vvs standard hydrogen electrode), light weight (0.534 g cm-3), and abundant reserves. They have become an ideal material for rechargeable lithium metal batteries (LMBs). However, low Coulomb efficiency, dendrite Li growth, and unlimited volume changes during Li deposition / dissolution result in poor electrochemical performance and safety issues. Replacing organic liquid electrolytes with solid electrolytes is expected to solve the problems of lithium-ion batteries and lithium metal anodes.

[0003] Polymer electrolytes (PEs) can suppress serious problems of lithium-ion batteries, such as electrolyte leakage, flammability, and lithium dendrite growth, to improve thermal and electrochemical stability, and therefore have been widely studied. Quasi-solid polymer electrolytes are composed of organic solvents as plasticizers, polymer matrices, lithium salts, and inorganic fillers. The properties of the polymer matrix, such as crystallinity, solubility, wettability, and swelling, directly affect the electrochemical properties of the system. Polyacrylonitrile (PAN), polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), and polyester (PMMA) are often used as polymer matrices for polymer electrolytes. Polymer electrolytes can not only improve the problems of large interfacial impedance and low ionic conductivity of solid electrolytes, but also reduce the safety risks caused by leakage of liquid electrolytes. However, each polymer matrix has corresponding disadvantages, and there are fewer varieties of quasi-solid polymer electrolytes that can be used in lithium / sodium ion battery systems. There is a lack of research on the influence of polymer matrix structure on battery electrochemical performance. Therefore, it has become an inevitable trend to develop a polymer electrolyte that retains the excellent electrochemical properties of liquid electrolytes while having high safety and stability.

[0004] The polymer quasi-solid electrolytes prepared by traditional non-in-situ methods have disadvantages such as poor interface contact and stability, and low ionic conductivity. The inability to simultaneously meet high ionic conductivity, high ion migration number, and good contact between electrode materials directly restricts the further development of QSE. Quasi-solid polymer electrolytes (QSEs) using in-situ polymerization are usually prepared by initially impregnating the inside of the electrode with a liquid precursor using thermal curing or UV curing methods. The in-situ method can better solve the interface problem between the electrode and the electrolyte, thereby improving the electrolysis efficiency. Summary of the invention

[0005] In view of the above problems, the purpose of the present invention is to provide a precursor solution, a method for preparing a quasi-solid polymer electrolyte and its application, and to prepare a quasi-solid polymer electrolyte in situ inside a battery by a thermal polymerization method. A polymer skeleton containing special functional groups is introduced to solve the interface contact problem caused by the preparation method and ion transport problems of the existing quasi-solid polymer electrolyte, which is of great significance for the development of a new type of flexible battery with good comprehensive performance.

[0006] To achieve the above object, the present invention provides a polyesteramine quasi-solid polymer electrolyte, wherein the polyesteramine quasi-solid polymer electrolyte comprises a polymer monomer and an electrolyte salt; The polymer monomer contains one or more of an ester compound containing an unsaturated bond and an amide compound containing a double bond, and the two are uniformly mixed in a certain ratio; The electrolyte salt is a lithium salt or a sodium salt.

[0007] The unsaturated bond ester compound is one or more of phosphonate or acrylate compounds.

[0008] The amide compounds are one or more amide compounds containing double bonds.

[0009] The phosphate ester is selected from a combination of one or more of acrylic acid phosphonate, methacrylic acid phosphate, alkyl acrylate phosphate, and hydroxyethyl methacrylate phosphate; The amide compound is selected from one or more of N, N-methylenebisacrylamide, N, N-dimethylformamide, propionamide, and acrylamide.

[0010] The concentration of the electrolyte salt is 0.5 M - 2 M, and the electrolyte is prepared by using one or more ester organic solvents.

[0011] The electrolyte also includes an initiator, which is selected from azobisisobutyronitrile, azobisisoheptanenitrile, and dibenzoyl peroxide, and the amount of the initiator is 0.05%-3%, the amount of the ester organic solvent is 70-98%, and the amount of the lithium salt or sodium salt is 5 wt%-10 wt%; The ester organic solvent is selected from a combination of one or more of dimethyl carbonate (DMC), ethyl acetate (EtOAc) and diethyl carbonate (DEC).

[0012] To achieve the above-mentioned purpose, the present invention also provides a method for in-situ preparation of a quasi-solid polymer electrolyte, wherein polymer monomers, salts, and solvents are configured in a certain proportion to form a precursor solution. The polymer monomers referred to above are one or more low molecular weight phosphonates or acrylate compounds containing special functional groups, one or more amide chemicals containing double bonds at the ends are used as crosslinking agents, the electrolyte salt is a sodium salt or a lithium salt, the initiator includes azobisisobutyronitrile (AIBN), and one or more battery-grade ester solvents are selected as organic solvents. The specific preparation process is as follows: S1 Under an argon protective atmosphere, two or more different polymer monomers, amide polymers with double bonds at both ends, and phosphonates or acrylate compounds are mixed in a certain proportion, stirred evenly, dissolved in one or more ester organic solvents, and a certain amount of electrolyte salt and initiator are added to prepare a precursor solution. The electrolyte salt is a lithium salt or a sodium salt; The phosphate ester is selected from a combination of one or more of acrylic acid phosphonate, methacrylic acid phosphate, alkyl acrylate phosphate, and hydroxyethyl methacrylate phosphate; The amide compound is selected from one or more of N, N-methylenebisacrylamide, N, N-dimethylformamide, propionamide, and acrylamide.

[0013] The concentration of the electrolyte salt is 0.5 M - 2 M, and the electrolyte is prepared by using one or more ester organic solvents.

[0014] The initiator in the electrolyte is selected from diisobutyronitrile, diisoheptyl azonitrile, and dibenzoyl peroxide, the amount of the initiator is 0.05%-3%, the amount of the ester organic solvent is 70-98%, and the amount of the lithium salt or sodium salt is 5 wt%-10 wt%; The ester organic solvent is selected from a combination of one or more of dimethyl carbonate (DMC), ethyl acetate (EtOAc) and diethyl carbonate (DEC).

[0015] S2 In an argon protective atmosphere, a series of precursor solutions with different monomer ratios prepared in step S1 are quantitatively injected into the battery by liquid injection, and a glass fiber diaphragm / PE diaphragm / PP diaphragm is used as a support to assemble a battery with lithium iron phosphate / ternary as the positive electrode material and lithium metal as the negative electrode.

[0016] S3 The assembled battery is left to stand at room temperature for a period of time. After the precursor solution completely soaks the separator and the electrode, the fully assembled battery is placed in an oven for in-situ thermal polymerization. The monomers are in-situ ring-opening polymerized or cross-linked polymerized under the thermal initiation of the initiator inside the battery to form a quasi-solid polymer electrolyte, thereby obtaining a polymer-based solid-state battery.

[0017] Preferably, the heating temperature is 60 - 120°C and the heating time is 60 - 120 min.

[0018] In general, the above synthesis method has the following effects compared with the existing synthesis methods: (1) The present invention adopts an in-situ thermal polymerization method that is different from the traditional non-in-situ synthesis of electrolytes. The precursor solution is configured to be injected into the battery system and in-situ polymerization is carried out inside the battery. This method has no limitation on the selection of monomers. The monomers used can be purchased from the market or polymerizable materials containing special functional groups that are easy to synthesize. Under high temperature conditions, ring-opening polymerization or cross-linking polymerization occurs under the action of an initiator to form a high molecular polymer skeleton.

[0019] (2) The monomers in the precursor solution of the present invention are one or more amide compounds and one or more phosphonates. Compared with the conventionally used ester electrolytes, the monomers in the precursor solution of the present invention have a more stable interface layer with the lithium metal negative electrode, which can effectively prevent further reaction with the metal negative electrode, thereby improving the stability of the battery.

[0020] (3) The in-situ thermal polymerization preparation method adopted by the present invention injects the precursor solution into the battery, assembles it into a complete battery, and then completes the polymerization inside the battery to form a quasi-solid polymer electrolyte. This method can construct a close contact electrode / electrolyte contact interface, greatly reducing the problem of ion transmission caused by interface contact, and improving the transmission efficiency of cations between the electrode and the electrolyte. This preparation method is simple, efficient and practical.

[0021] (4) The polymer monomers containing special functional groups selected by the present invention, under heating conditions, the thermal initiator initiates the ring-opening cross-linking polymerization of the polymer monomers to form a macromolecular skeleton. The special atomic structure contained in this polymer skeleton can combine with cations, which is beneficial to the migration of ions. At the same time, the polymer monomers partially decompose to form a stable solid electrolyte phase interface layer, and the formed interface layer is beneficial to the conduction of cations, so that the battery system formed by the quasi-solid polymer electrolyte has a wide electrochemical window, a high ion migration number and ion conductivity, and has the potential to match high-voltage positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic diagram of the preparation of the quasi-solid polymer electrolyte and the battery assembly provided by the present invention.

[0023] Figure 2 This is a graph of the ion migration number of the polyesteramine quasi-solid polymer electrolyte provided in Example 2 of the present invention.

[0024] Figure 3 This is a Fourier infrared spectrum of the quasi-solid polymer electrolyte provided in Example 2 of the present invention.

[0025] Figure 4 These are electron scanning microscope images of the polyesteramine quasi-solid polymer electrolyte provided in Example 2 of the present invention at different magnifications.

[0026] Figure 5 This is the electrochemical window diagram of the polyesteramine quasi-solid polymer electrolyte provided in Example 2 of the present invention.

[0027] Figure 6 These are optical images of three different proportions of polyesteramine quasi-solid polymer electrolytes provided in Examples 1-3 of the present invention. DETAILED DESCRIPTION

[0028] In order to make the purpose of the present invention and the technical synthesis scheme clearer, the present invention will be further described in more detail below in conjunction with the accompanying drawings and embodiments. A method for preparing a polyesteramine quasi-solid polymer electrolyte is provided, comprising the following steps: The quasi-solid polymer electrolyte of the present invention needs to be combined with the battery assembly process during the specific preparation process. The raw materials for preparing the quasi-solid polymer electrolyte are mixed and configured in a certain proportion to form a uniform precursor solution, and then the precursor solution is injected into the battery in the form of an "electrolyte" to complete the assembly of the battery. The fully assembled battery is placed in a vacuum heating oven, and the precursor solution is polymerized by heating to obtain a quasi-solid polymer electrolyte. This will be explained below in conjunction with specific implementation examples.

[0029] Example 1: Synthesis of 10 wt% polyesteramine (10% QSE) quasi-solid polymer electrolyte Step S1: Preparation of 2 M LiClO4 / EC / DMC / EMC electrolyte: A fixed mass of lithium perchlorate (LiClO4) and a carbonate organic solvent (a mixture of EC, DMC, and EMC in a volume ratio of 1:1:1) are mixed and stirred until a 2 M LiClO4 / EC / DMC / EMC electrolyte solution is formed after being uniformly mixed, and the solution is placed in an argon-filled glove box for use.

[0030] Step S2: 2 M LiClO4 / EC / DMC / EMC electrolyte containing 3 wt % AIBN: Azobisisobutyronitrile (AIBN), LiClO4 and an ester organic solvent were mixed and stirred until uniformly mixed to form a 2 M LiClO4 / EC / DMC / EMC electrolyte containing 3 wt % AIBN, which was placed in an argon-filled glove box for use.

[0031] Step S3: Synthesis of 10wt% polyesteramine electrolyte precursor solution: First, accurately weigh the monomers of acrylic acid phosphonate AP and N,N-methylenebisacrylamide MBA (n(AP):n(MBA)=1:1), with a total mass of 10 wt%, and place them in a 3 mL sample bottle. Seal the weighed sample bottle and bring it into the glove box.

[0032] In a glove box, accurately weigh a certain mass of 2 M LiClO4 / EC / DMC / EMC with 3 wt % AIBN and add 2 MLiClO4 / EC / DMC / EMC electrolyte to a fixed mass. This ratio ensures that the mass ratio of the total amount of monomers to the electrolyte reaches 10:90. After weighing, seal the bottle mouth and shake it thoroughly to obtain a precursor solution of the quasi-solid polymer electrolyte for use.

[0033] Step S4: Preparation of 3 wt % PVDF solution of binder. Accurately weigh white polyvinylidene fluoride (PVDF) powder on an analytical balance, dissolve it in a clean small bottle containing 1-methyl-2-pyrrolidone (NMP), put in a magnetic rod, and stir continuously until the powder is completely dissolved and the solution is transparent. Seal the bottle mouth and set aside (do not prepare in large quantities, as it will easily absorb water if left for a long time).

[0034] Step S5: Preparation of positive electrode material lithium iron phosphate (LFP) electrode sheet. Accurately weigh the dried LFP on the analytical balance, add the conductive agent Super P, and continuously stir the prepared 3 wt % PVDF binder in a mortar until it is evenly mixed. Add an appropriate amount of NMP solvent to dilute the slurry until it has a certain viscosity and is uniform. Adjust the scraper to the required height, evenly disperse the slurry on the pre-laid positive electrode collector aluminum foil, and push the scraper at a uniform speed to disperse the slurry. Transfer to a 60 ° C forced air drying oven and dry for more than 4 h, and use a punching machine with a specification of 13 mm to punch out the positive electrode sheet of the required diameter. The active material (positive electrode material lithium iron phosphate) loading range is 1.5 - 2.0 mg cm -2 , and transferred to a glove box filled with argon for later use.

[0035] Step S6: According to the conventional assembly method of LFP lithium-ion batteries, in an argon atmosphere, the positive electrode shell, positive electrode sheet, precursor solution, glass fiber as support and lithium metal as negative electrode are assembled in order, and left to stand for a period of time at room temperature. After the precursor solution soaks the electrode, the complete battery is placed in a vacuum blast drying oven at 120 ° C for thermal polymerization for 80 minutes. The precursor solution is in situ ring-opening polymerized inside the battery to form a quasi-solid polymer electrolyte, forming a 10 wt% polyester amine (10% QSE) type mixed-base polymer-based solid-state battery. The specific synthesis steps are as follows: Figure 1 .

[0036] Example 2: Synthesis of 5 wt% polyesteramine (5% QSE) quasi-solid polymer electrolyte Step S1: Synthesis of esteramine mixed quasi-solid polymer electrolyte. First, weigh a certain amount of acrylic acid phosphonate and MBA and place them in a 3 mL sample bottle. The ratio of the two polymer monomer substances is 1:1, and the total mass of the polymer monomer accounts for 5 wt%. After the sample is weighed, seal the sample bottle and bring it into a glove box filled with argon atmosphere. Accurately weigh 3 wt% AIBN LiClO4 / EC / DMC / EMC (about 1% of the total amount of monomer substances) in the glove box and add 1 M LiClO4 / EC / DMC / EMC electrolyte to a fixed amount. The total mass of the polymer monomer accounts for 5%. This ratio ensures that the ratio of monomer to electrolyte reaches 5:95. After weighing, seal the bottle mouth and shake it thoroughly to obtain the electrolyte precursor solution for use.

[0037] Step S2: Same as step S6 in Example 1. According to the conventional assembly method of LFP lithium-ion batteries, in an argon atmosphere, the positive electrode shell, the positive electrode plate, the precursor solution, the glass fiber as the support and the lithium metal as the negative electrode are assembled in order, and left to stand for a period of time at room temperature. After the precursor solution soaks the electrode, the complete battery is placed in a vacuum blast drying oven at 80 ° C for thermal polymerization for 80 min. The precursor solution is in-situ ring-opening polymerized inside the battery to form a quasi-solid polymer electrolyte, forming a 5 wt% polyester amine (5% QSE) type mixed-base polymer-based solid-state battery, and the relevant properties of the electrolyte at this ratio are tested, such as Figure 2-5 .

[0038] Example 3: Synthesis of 2 wt% polyesteramine (2% QSE) quasi-solid polymer electrolyte Synthesis of ester-amine mixed quasi-solid polymer electrolyte. First, weigh a certain amount of AP and MBA and place them in a 3 mL sample bottle so that the ratio of the amount of substance of the two polymer monomers is 1:1, and the total mass of the polymer monomers accounts for 2%. After the sample is weighed, seal the sample bottle and bring it into a glove box filled with argon atmosphere. In the glove box, accurately weigh 3 wt% AIBN LiClO4 / EC / DMC / EMC (about 1% of the total amount of monomer substance) and add 1 M LiClO4 / EC electrolyte to a fixed amount. The total mass of the polymer monomer accounts for 2%. This ratio ensures that the ratio of monomer to electrolyte reaches 2:98. After weighing, seal the bottle mouth and shake it thoroughly to obtain the electrolyte precursor solution for use. And assemble the experimental battery in the same way as step S2 of Example 2. Figure 6 As shown in the figure, the quasi-solid inversion formed by 2% QSE does not flow in the short term, but there is liquid extravasation and it is difficult to maintain a stable solid state. In comparison, its solid-liquid properties are poor. The main reason is that the polymer skeleton formed by the low monomer content is not enough to cover the liquid electrolyte. Therefore, it is further speculated that in order to obtain a structurally complete gel polymer electrolyte, the monomer content must be greater than 2% of the total mass.

[0039] The present invention prepares a quasi-solid polymer electrolyte. By utilizing the fluidity of the liquid, the liquid precursor is first used to fully wet each interface of the solid-state battery, and then the polymer electrolyte is generated by in-situ polymerization, which can effectively improve the compatibility of the solid-solid interface in the all-solid-state battery. Through the connection of double bonds, special functional groups are introduced to form a functional polymer skeleton, and the resulting quasi-solid electrolyte has a stable structure, a wide electrochemical window, and a high ion migration number. In addition, the electrolyte is applied to the lithium battery system to assemble LiFePO4‖Li batteries, which shows good cycle performance and rate performance. The LSV test shows that there is a wide electrochemical window (5 V), indicating that it has the potential to match high-voltage electrode materials. The large number of EO groups contained in the polymer matrix can interact with lithium ions and promote the transmission of ions, thereby obtaining a high ion migration number (0.54), which can greatly reduce the concentration polarization of the system during the charge and discharge process, and also delay the time for the appearance of lithium dendrites as much as possible. The method for preparing a quasi-solid polymer electrolyte in situ of the present invention is suitable for the polymerization of different types of monomers, and the electrolyte can be matched with different types of electrodes, and has a very broad application prospect. The preparation method of the quasi-solid polymer electrolyte of the present invention is simple and rapid, can be matched with the existing battery production process, is conducive to large-scale preparation, and the prepared polymer-based solid-state battery has good performance.

[0040] The above embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here, so the obvious changes or modifications derived are still within the protection scope of the invention.

Claims

1. A polyesteramine quasi-solid polymer electrolyte, characterized in that: The polyesteramine quasi-solid polymer electrolyte comprises a polymer monomer and an electrolyte salt; The polymer monomer contains one or more of an ester compound containing an unsaturated bond and an amide compound containing a double bond, and the two are uniformly mixed in a certain ratio; The electrolyte salt is a lithium salt or a sodium salt.

2. The polyesteramine quasi-solid polymer electrolyte according to claim 1, characterized in that: The unsaturated bond ester compound is one or more of phosphonate or acrylate compounds.

3. The polyesteramine quasi-solid polymer electrolyte according to claim 2, characterized in that: The amide compounds are one or more amide compounds containing double bonds.

4. The polyesteramine quasi-solid polymer electrolyte according to claim 2, characterized in that: The phosphate ester is selected from a combination of one or more of acrylic acid phosphonate, methacrylic acid phosphate, alkyl acrylate phosphate, and hydroxyethyl methacrylate phosphate.

5. The polyesteramine quasi-solid polymer electrolyte according to claim 3, characterized in that: The amide compound is selected from one or more of N, N-methylenebisacrylamide, N, N-dimethylformamide, propionamide, and acrylamide.

6. The polyesteramine quasi-solid polymer electrolyte according to claim 1, characterized in that: The concentration of the electrolyte salt is 0.5 M - 2 M, and the electrolyte is prepared by using one or more ester organic solvents.

7. The polyesteramine quasi-solid polymer electrolyte according to claim 6, characterized in that: The electrolyte also includes an initiator, which is selected from azobisisobutyronitrile, azobisisoheptanenitrile, and dibenzoyl peroxide, and the amount of the initiator is 0.05%-3%, the amount of the ester organic solvent is 70-98%, and the amount of the lithium salt or sodium salt is 5 wt%-10wt%; The ester organic solvent is selected from a combination of one or more of dimethyl carbonate DMC, ethyl acetate EtOAc and diethyl carbonate DEC.

8. A method for preparing the polyesteramine quasi-solid polymer electrolyte according to any one of claims 1 to 7, characterized in that: The steps include: S1. In an argon protective atmosphere, one or more monomers and an electrolyte salt in a certain equivalent ratio are uniformly mixed to obtain a precursor solution; wherein the polymer monomer is one or more low-polymerization degree phosphonate or acrylate compounds containing functional functional groups and amide compounds containing double bonds; and the electrolyte salt is a lithium salt or a sodium salt; S2, under an argon protective atmosphere, injects the precursor solution prepared by S1 into the battery by injecting liquid into the battery, and assembles the battery with glass fiber diaphragm / PE diaphragm / PP diaphragm as support and matching with electrode materials; S3 leaves the assembled lithium / sodium battery to stand at room temperature for a period of time, and after the precursor solution has soaked the electrode, it is placed in a vacuum drying oven for heating and polymerization to form a quasi-solid polymer electrolyte, thereby obtaining a polymer-based solid-state battery.

9. The method for preparing the polyesteramine quasi-solid polymer electrolyte according to claim 8, characterized in that: The heating polymerization reaction temperature is 60-120°C; the reaction time is 20-100 min.